The Impact of Negative Family Environment and Depression on Running Away From Home Among Korean Adolescents - Baek, Hyunin (International criminal justice review, 2017)
Using general strain theory (GST), this study examines negative stimuli (poor relationship with family, parental child abuse, and poor parenting), with the mediating effect of negative emotion (depression), on the deviant behavior of running away from home. The current study used data from a 2009 Korean survey of 9,750 adolescent students in a structural equation model, to examine the possible mediating role of negative emotions. The research results showed that a poor relationship with family and parental abuse increases the level of depression. Also, the level of depression that was experienced by juveniles influenced the likelihood of running away from home. Therefore, this study supported the GST hypothesis of negative stimuli impacting juvenile delinquency with a mediating effect of negative emotion. This study suggests that it is important to remove negative stimuli in the family environment to reduce depression and running away from home.